THE ROLE OF ELEMENTARY SCHOOL PRINCIPALS IN DEVELOPING ACTIVE AND CREATIVE DIGITAL-BASED LEARNING INNOVATIONS - Ramisah, Ramisah (Jurnal Kajian Pembelajaran dan Keilmuan, 2025)
This study analyzes the role of the principal in developing digital-based active and creative learning innovations at SD Negeri 13 Nanga Tayap, West Kalimantan. Using a qualitative case study approach, data were collected through in-depth interviews, classroom observations, and documentation. The selection of informants employed a purposive sampling technique, involving the principal, teachers, and administrative staff considered to have the most relevant insights into the implementation of digital learning innovation. Data were analyzed using the Miles and Huberman interactive model, consisting of data reduction, data display, and conclusion drawing. The findings show that the principal demonstrates transformative, participatory, and adaptive leadership in empowering teachers through internal digital training, mentoring, and collaboration with external partners. Despite limited infrastructure and internet access, the principal initiated creative strategies such as offline learning media and community-based digital training. This leadership resulted in improved teacher professional competence, enhanced digital literacy, and increased student engagement and motivation. The study concludes that visionary and innovative principal leadership is crucial in driving digital-based educational transformation, especially in rural schools with limited resources.